Use of Learning Media in Increasing Understanding of Islamic Cultural History (SKI) at MI Cikoredas School - Nuranisa Nuranisa; Ulfatussa’diyah Ulfatussa’diyah; Siti Fatihah; Nur Abdillah Maulana; Adi Rosadi (Madrasah Al-Wathoniyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study examines the use of learning media to enhance students’ understanding of the Islamic Cultural History subject at MI Cikoredas. The main issue addressed is the low level of student comprehension resulting from the dominance of lecture-based methods without the support of engaging and contextual media. The purpose of this research is to determine the effectiveness of learning media in strengthening students’ understanding and to describe teachers’ strategies in implementing it. This study employed a descriptive qualitative approach with data collected through interviews and observations involving teachers, the principal, and students. The results indicate that the use of learning media such as instructional videos, illustrative images, and interactive presentations increases students’ enthusiasm, participation, and retention of Islamic historical events. Visual and audiovisual media have been proven to help students grasp abstract concepts more concretely and engagingly. The conclusion emphasizes that learning media play a significant role in creating a more meaningful, enjoyable, and contextual Islamic Cultural History learning process. The implication of this study is the need for teachers to enhance their creativity in selecting and developing relevant learning media that suit students’ characteristics and meet the demands of digital-era education.